Grave new world : the end of globalization, the return of history - King, Stephen D. (New Haven, CT : Yale University Press, 2017)
Combining historical analysis with current affairs, economist Stephen D. King provides an account of why globalization is being rejected, what a world ruled by rival states with conflicting aims might look like, and how the pursuit of nationalist agendas could result in a race to the bottom. King argues that a rejection of globalization and a return to "autarky" will risk economic and political conflict. He uses lessons from history to see how best to avoid the worst possible outcomes
Includes bibliographical references and index.
nmn, 10/01/2019, ijb, 28/01/2019
Loans
Keywords: Globalization; International economic relations; Globalization--Economic aspects; Nationalism--Economic aspects; Protectionism; Anti-globalization movement; International economic integration